The Effect of Antibacterial and Waterproof Coating Prepared From Hexadecyltrimethoxysilane and Nano-Titanium Dioxide on Wood Properties - Yang, Lechen; Wu, Yan; Yang, Feng; Wang, Wenhao (Frontiers in Materials, 2021)
As one of the most sustainable resources, wood has been widely used in the fields of construction, decoration, flooring and furniture. However, the micron-scale porous structure of wood makes it have strong moisture absorption capacity and is susceptible to bacterial adhesion. In order to expand its utility in more applications of wood products, it is necessary to make the wood have a certain antibacterial and waterproof properties. This study demonstrates a method of using hexadecyltrimethoxysilane and nano-titanium dioxide to prepare antibacterial and waterproof coating and apply it to wood surfaces. Studies have shown that this kind of wood coated with an antibacterial waterproof coating has excellent antibacterial properties (antibacterial rate as high as 99%) and waterproof properties, it can still maintain a water contact angle of nearly 80° after stirring in water for 10 minutes. In addition, this antibacterial and waterproof coating does not cause a major change in the color of the wood, and at the same time increase the tensile strength and hardness to a certain extent. The above-mentioned properties of this antibacterial and waterproof coating provide a new idea for the preparation of wood coatings.